Defining functional microbiomes of wheat (Triticum aestivum) and maize (Zea mays), under regenerative management practices, in South Africa - Page, Lucan Dylan (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.